Clinical Guidelines of the Egyptian Psychiatric Association for the Management of Treatment-Resistant Unipolar Depression in Egypt - Abdel-Wahab, Momtaz; Okasha, Tarek; Shaheen, Mostafa; Nasr, Mohamed; Molokheya, Tarek; Omar, Abd ElNasser; Rabie, Menan A.; Samy, Victor; Hamed, Hany; Ali, Mohamed (Frontiers in Psychiatry, 2022)
Background Major depressive disorder (MDD) is a public health burden that creates a strain not only on individuals, but also on the economy. Treatment-resistant depression in the course of major depressive disorder represents a clinically challenging condition that is defined as insufficient response to two or more antidepressant trails with antidepressants of the same or different classes that were administered at adequate daily doses for at least 4 weeks. Objective/Hypothesis To develop a treatment guideline for Treatment Resistant Depression (TRD). Methodology Experts in the field gathered and reviewed the available evidence about the subject. Then, a series of meetings were held to create recommendations that can be utilized by Egyptian psychiatrists. Results The guidelines provide recommendations in various clinical settings. It evaluates different situations, such as patients at risk of resistance, those with resistance and recommends strategies to resolve the clinical case. Conclusion The consensus guidelines will improve the outcomes of patients, as they provide recommendations across various domains that are of concern for the practicing psychiatrist.